New Developmentalism and the EU’s Carbon Border Adjustment Mechanism: Policy Options for the Global South - Ikhlas Tawazun; Natasya Dewi Shafira (Institute of International Studies, 2021)
The Carbon Border Adjustment Mechanism (CBAM), put forward by the European Union (EU), appeared as a new environmental trade policy that holds significance to the Global South. It necessitates the Global South countries to make changes in their development strategies to not only adapt to the CBAM, but to the overall shifting of the world’s economic growth pattern and sustainable development agenda from which it emerged. Against this backdrop, this article addresses how the Global South can adapt to the CBAM in particular and the larger pressure to transition to a more sustainable growth and development. This article uses qualitative methodology with data acquired through extensive desk research. Findings of this article show that new developmentalism is well suited to enhance the needed policy changes as the Global South can leverage its already-existing state capacity to effectively steer the transformation towards a more sustainable growth. This article is also equipped with possible policy options for the Global South as close examinations towards existing development policies of several Global South countries still list several challenges.